PENGARUH INDEPENDENSI DEWAN KOMISARIS DAN STRUKTUR KEPEMILIKAN PERUSAHAAN TERHADAP KETEPATAN WAKTU PELAPORAN INFORMASI PERUSAHAAN MELALUI INTERNET (Studi Kasus pada Perbankan yang Terdaftar di Bursa Efek Indonesia) - Edwardus Randy Ekha Mahendra; Siti Mutmainah (Diponegoro Journal of Accounting, 2013)
This study aims to examine and analyze the influence of board independence and corporate ownership structure to the timeliness of corporate internet reporting (TCIR) in banking companies. The timeliness of corporate internet reporting are measured with Abdelsalam and El-Masry’s TCIR criterias, adjusted to the rules and characteristics of companies in Indonesia. Board independence are measured by two variables, percentage of independent directors and average tenure of directors . Corporate ownership structures are measured by three variables, blockholders ownership, director ownership, and CEO ownership. This study is undertaken using documentary method and using data from annual reports and company website . It uses multiple regression technique as method of analysis. There are 30 banking companies listed on IDX in 2011 used as sample. The result of this study indicates that CEO ownership is positive significant influence to TCIR. Increase CEO ownership, the company will increase their TCIR levels. The difference results is indicated by percentage independent directors, average tenure of directors, blockholders ownership, and directors ownership that don’t have significant influence to TCIR.